1981
DOI: 10.1111/j.1471-4159.1981.tb01722.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Free Translation of Free and Membrane‐Bound Polysomes and Polyadenylated mRNA from Rabbit Brain Following Administration of d‐Lysergic Acid Diethylamide In Vivo

Abstract: Free and membrane-bound polysomes and polyadenylated mRNA isolated from rabbit brain were translated in an mRNA-dependent rabbit reticulocyte lysate system. Electrophoretic analysis of the cell-free translation products demonstrated that although most of the nascent proteins were common to both free and membrane-bound brain polysomes, qualitative and quantitative differences were observed. Compared with the results obtained with purified polyadenylated mRNA, the addition of intact polysomes to the cell-free tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Free polysomes were prepared as described (11) Ranu and London (12). The lysate was treated with micrococcal nuclease and utilized in a cell-free translation system essentially as described by Pelham 5-,l aliquots were removed and diluted into 1 ml of ice-cold distilled H20.…”
Section: Methodsmentioning
confidence: 99%
“…Free polysomes were prepared as described (11) Ranu and London (12). The lysate was treated with micrococcal nuclease and utilized in a cell-free translation system essentially as described by Pelham 5-,l aliquots were removed and diluted into 1 ml of ice-cold distilled H20.…”
Section: Methodsmentioning
confidence: 99%
“…Although cultured cells have been used in most of the studies of mammalian stress proteins, they have been induced in rats by heat (Currie and White, 1981) and arterial ligation (Currie and White, 1981;Hammond et al, 1982), in rabbits by d-lysergic acid diethylamide-stimulated hyperthermia (Heikkila et al, 1981), and in humans following major surgery (Anderson et al, 1982). Therefore, it is likely that stress proteins have roles in responses of animals to trauma.…”
mentioning
confidence: 99%
“…For example, it has been suggested that the synthesis of heat shock proteins is correlated to the phenomenon of acquired thermotolerance (4)(5)(6)(7). The induction of heat shock proteins is relevant to the intact mammal, since increases in body temperature similar to those attained during fever induce synthesis of a heat shock protein of 70-74 kDa in the mammalian brain and other organs (8)(9)(10)(11)(12)(13)(14)(15)(16). Because these proteins may be involved in the response of the body to fever reactions, it is important to increase our understanding of heat shock proteins in intact Mammalian organs.…”
mentioning
confidence: 99%
“…Aliquots were lyophilized to dryness and solubilized in 9.5 M urea/2% (vol/vol) Nonidet P-40/0.8% (wt/vol) ampholytes, pH 3-10/5% 2-mercaptoethanol. Isoelectric focusing (first dimension) was performed in 10-mm cyclindrical gels containing 4% acrylamide, 9 M urea and 2% ampholytes, pH 3-10. Cathode and anode buffers were 20 mM NaOH (degassed) and 10 mM H3PO4, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation